A review of surface integrity in machining and its impact on functional performance and life of machined products. (3rd July 2008) - M'Saoubi, R.; Outeiro, J.C.; Chandrasekaran, H.; Dillon Jr., O.W.; , I.S. Jawahir
This paper presents an overview of the past research on Surface Integrity (SI) studies in the context of machined components from a range of work materials including stainless steels, Ni and Ti alloys, hardened steels for dies and moulds, bearings and automotive applications. Typical surface alterations such as phase transformations, microhardness and residual stress are discussed and correlated with the functional performance of the machined products. A summary of past and current modelling efforts is then presented along with projections for developing predictive models for SI and means for enhancing product sustainability in terms of its functional performance.